Factors affecting mothers' activeness in attending classes for pregnant women - Idawati; Yuliana; Susi Andriani (Institute of Computer Science (IOCS), 2023)
The government implemented a class program for pregnant women to reduce maternal mortality. The participation of pregnant women and their families in pregnant women's classes is expected to increase knowledge and influence the behavior of pregnant women. The purpose of this study was to determine the factors that influence the activeness of mothers in attending classes for pregnant women. This research is analytic in nature. The population is all pregnant women in the working area of the Mutiara Barat Public Health Center, totaling 439 pregnant women, and the sample in this study was 81 pregnant women. The sampling technique is accidental sampling. The results showed that there was an effect of knowledge on the activity of the mother in taking classes for pregnant women (p value = 0.001), and there was an effect of family support on the activity of the mother in attending classes for pregnant women (p value = 0.013). (p = 0.006), and there is a motivational effect on the activeness of mothers in attending classes for pregnant women (p = 0.006). It is recommended that pregnant women be active in conducting class visits for pregnant women so that pregnant women can obtain correct information about pregnancy, childbirth, postpartum care, and good baby care.